A new Corononcodes Speiser from the Palaearctic Region, with a key to species (Diptera: Acroceridae) - Kehlmaier, Christian; Gharali, Babak; Jahromi, Bahareh Majnon (Zootaxa, 2014)
Corononcodes ziegleri spec. nov. is described and illustrated based on material from Iran. The species represents the second Palaearctic representative of this panopine genus. In addition, C. siculus Bezzi is recorded from Fuerteventura (Canary Islands, Spain) for the first time. An identification key to the Palaearctic species of Corononcodes is presented. Additional faunistic records for the Iranian fauna comprise Acrocera orbiculus (Fabricius) and an apparently undescribed species of Ogcodes Latreille. DNA-barcodes for all Iranian taxa are provided.